2019
DOI: 10.1016/j.tsf.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of superhydrophobic coatings on AISI 304 austenitic stainless steel with different surface pretreatments

Abstract: In the context of increasing industrial importance of superhydrophobic surfaces, three different pretreatments on an austenitic stainless steel surface have been tested to be coated with a silane-based solution containing SiO 2 nanoparticles, in order to obtain superhydrophobic surfaces. The pretreatments are (i) an acetone degreaser, (ii) this one followed by a hot air treatment and acid pickling, and (iii) the previous one followed by an alkaline etching. Pretreated surfaces have been characterized by X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Pickling of the surface allows to obtain a fairly high roughness, which promotes lubricant retention [20]. Change from a hydrophilic behavior, typical of a stainless steel surface with a smooth finishing, to a hydrophobic behavior, resulting from a rough surface at the micro/nano scale, has been obtained by chemical treatments [21][22][23], electrochemical treatments [24,25], femtosecond laser treatments [26,27], and low-energy laser shock peening [28]. The increase of surface roughness has drawbacks: in chloride-ion containing solutions the corrosion resistance tends to decrease as the surface roughness increases [29,30], so that for applications which require very high corrosion resistance, as for stents and implants, a smooth surface, obtained with electrochemical polishing, is preferred [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Pickling of the surface allows to obtain a fairly high roughness, which promotes lubricant retention [20]. Change from a hydrophilic behavior, typical of a stainless steel surface with a smooth finishing, to a hydrophobic behavior, resulting from a rough surface at the micro/nano scale, has been obtained by chemical treatments [21][22][23], electrochemical treatments [24,25], femtosecond laser treatments [26,27], and low-energy laser shock peening [28]. The increase of surface roughness has drawbacks: in chloride-ion containing solutions the corrosion resistance tends to decrease as the surface roughness increases [29,30], so that for applications which require very high corrosion resistance, as for stents and implants, a smooth surface, obtained with electrochemical polishing, is preferred [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these reports discuss the chemical inertness and good adherence of the TEOS based coatings on SS 44 . Whereas there are limited reports on only TEOS coating on SS but always a silane is used to modify the surface 45 in order to obtain superhydrophobic property. Liang et al 46 reported the self assembly of nanometer sized silica particles on aluminium substrate through the hydrolysis of TEOS and then these silica particles were modified with vinylsiloxane; surface roughness is provided by TEOS and low surface energy modification was achieved by using a low surface energy material, siloxane.…”
Section: Resultsmentioning
confidence: 99%
“…An intermediate state, where the liquid partially wets the surface is also commonly encountered [6]. The chemical modification of metallic surfaces to render them hydrophobic has been investigated using different methods like the sol-gel method [7,8], direct immersion in a reactive hydrophobic solution [9], electrodeposition [10], thermal plasma evaporation [11], and Plasma Enhanced-Chemical Vapor Deposition (PE-CVD) [12].…”
Section: Introductionmentioning
confidence: 99%